Career Preparation Class: Kembangkan Potensimu, Raih Karir Impianmu - Qatrunnada, Rizqi Zulfa; Anisah Hanifah Dzakiyyah; Afkarina, Wafa Azka; Ridhiawan, Falah (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2025)
The lack of work readiness among university graduates contributes to the rising unemployment rate. This is due to a lack of understanding of basic skills, limited awareness of personal potential and career direction, and a lack of preparation for writing CVs and interviews. To address these issues, a 240-minute career preparation training session was held for 43 final-year students and recent graduates. The training covered motivation and work competencies, exploring personal potential, CV preparation and interview strategies. The effectiveness of the training was measured through reaction and learning evaluations. The results showed high levels of satisfaction among participants in various areas, as well as a significant increase in learning scores (p < .001). These findings can be used to inform students' career preparation and to help universities design programmes, counselling services and collaborations with industry and alumni that provide relevant, practice-based training.